A Retrospective Study of Ultrasound Characteristics and Macroscopic Findings in Confirmed Malignant Pleural Effusion - Piskac Zivkovic, Nevenka; Cikara, Igor; Novak, Nina Petra; Brkljacic, Boris; Tudoric, Neven (Pulmonary Medicine, 2019)
Background. A definitive diagnosis of malignant pleural effusion (MPE) is reached by cytological or histological assessment, but thorough analysis of the ultrasound features of the effusion as well as pleural thickening or nodularity can also be of significant diagnostic help. Objective. To assess the relationship of specific ultrasound characterisctics and macroscopic features of confirmed malignant pleural effusion, thus increasing the diagnostic potential of thoracic ultrasound. Methods. The findings of thoracic ultrasonography performed prior to initial thoracentesis in 104 patients with subsequently confirmed malignant pleural effusion were analyzed with regard to the macroscopic features of the pleural effusion. Results. Distribution in terms of frequency of hemorrhagic/sanguinolent (n=64) in relation to nonhemorrhagic transparent/opaque (n=40) MPE, regardless of their ultrasound characteristics, did not yield a statistically significant correlation (p=0.159). Conversely, the frequency distribution of hemorrhagic pleural effusions (n=8) in relation to nonhemorrhagic effusions (n=1), in the group of septated MPE, showed a statistically significant difference (p<0.001). The least number of patients (0.96%) had a complex septated MPE combined with the macroscopic appearance of a serous/transparent nonhemorrhagic effusion, which suggests that this combination is a sporadic occurrence and may have a diagnostic significance for this patient group. Conclusion. The incidence of specific combinations of the ultrasound characteristics and macroscopic appearance of MPEs showed different frequency distributions, which may improve the diagnostic value of thoracic ultrasound in this patient population.